Consumer Responses to Scarcity Appeals in Online Ordering - Hariyana, Nanik; Izaak, Wilma Cordelia; Sholihah, Dienni Ruhjatini (Future Science, 2023)
Scarcity appeals, which highlight how a commodity or service is scarce due to